(untitled) (Samriddhi Journal of Development Studies, 2024)
The geopolitical environment and the constraints of contemporary warfare are being redefined by the emergence of space as a new frontier of strategic relevance. This study examines how the idea of space warfare has changed over time, using secondary sources to examine its historical evolution, contemporary patterns, and potential ramifications. Driven by developments in satellite technology, anti-satellite weaponry (ASATs), and space-based surveillance systems, the study emphasizes the strategic importance of space as a domain for operations and a medium for force projection. With an emphasis on the major players—including the US, Russia, China, and up-and-coming space faring countries—who are aggressively investing in space capabilities to attain strategic dominance, the research emphasizes the militarization of space. Particular attention is paid to the fact that space technologies are dual-use, making it difficult to distinguish between military and civilian uses and increasing the likelihood of conflict escalation. Along with examining the ethical and legal aspects of space warfare, the article critiques current frameworks, such as the 1967 Outer Space Treaty, which falls short in addressing modern issues. The study uses an interdisciplinary method to investigate how space combat affects economic stability, technological innovation, and international security. The results show how urgently international cooperation is needed to set rules and procedures for the peaceful use of space. The research also addresses how space war might start an arms race, which would have unanticipated effects both on Earth and on other planets. This study offers a thorough grasp of the intricacies and stakes of space warfare by combining knowledge from military studies, international law, and technology analysis. In order to guarantee that space continues to be a place for peaceful exploration rather than a battlefield, it ends by promoting strong governance frameworks and global discussion.